2016
DOI: 10.4081/aiua.2016.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Transperitoneal laparoscopic treatment for recurrence of a giant multilocular prostatic cystadenoma: A case report and review of the literature

Abstract: Giant multilocular prostatic cystadenomas (GMPC) are very rare benign tumors that originate from the prostate with extensive spread into the pelvis. The lesion may present as large abdominal mass causing obstructive voiding dysfunction and usually not invading adjacent structures. All of the previously reported patients with GMPC underwent open surgery. Although the natural history of prostatic cystadenoma remains unknown, complete surgical excision may not always be necessary. We report the case of a 74-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…In a review of the previous literature on such cases, several treatment modalities for giant multilocular prostatic cystadenoma have been reported, including conservative treatment such as gonadotropin-releasing hormone (GnRH) antagonist[ 12 ], transurethral resection[ 13 ] or enucleation of the prostate, laparoscopic cyst resection[ 14 ], partial or complete tumor resection, even radical prostatectomy or pelvic exenteration. For now, the general consensus of management is complete surgical excision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review of the previous literature on such cases, several treatment modalities for giant multilocular prostatic cystadenoma have been reported, including conservative treatment such as gonadotropin-releasing hormone (GnRH) antagonist[ 12 ], transurethral resection[ 13 ] or enucleation of the prostate, laparoscopic cyst resection[ 14 ], partial or complete tumor resection, even radical prostatectomy or pelvic exenteration. For now, the general consensus of management is complete surgical excision.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study reported that a GnRH antagonist was effective for the treatment of recurrent GMC of the prostate, and it was not feasible for that patient to undergo invasive surgery. Nonetheless, no recurrences were reported during the different follow-up periods reported in patients who underwent TURP[ 13 ] and cyst resection[ 14 ]. Furthermore, in most known situations, incomplete resection could result in recurrence despite the benign nature of the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 ] Occasionally, constipation caused by mechanical compression of the rectum can be seen. [ 8 ] These manifestations are suggestive of a lower urinary tract disease but not specific, similar to the features of prostate hyperplasia. Elevated serum PSA is commonly seen in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, CT or MRI might reveal components of the tumor and its relationship with adjacent organs, which is crucial for the optimal determination of surgical procedure. [ 8 ] GMPC is often characterized with multilocular masses in the pelvis. The septa in the cyst are often irregularly thickened.…”
Section: Discussionmentioning
confidence: 99%